2018
DOI: 10.1080/01431161.2018.1500072
|View full text |Cite
|
Sign up to set email alerts
|

Very high resolution mapping of coral reef state using airborne bathymetric LiDAR surface-intensity and drone imagery

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 28 publications
0
46
1
Order By: Relevance
“…The quantitative analysis of agreement with the baseline map showed that both methods, despite being very different in terms of input data and methodology, gave comparable results regarding map agreement and error. The map agreement of 67% (OBIA) and 69% (BTM) is acceptable, although lower than what has been reported in some recent studies that mapped reef [28][29][30]. These differences might be related to various factors, e.g., shallow warm-water coral reefs can be mapped with satellite or drone-based optical sensors, which give more spectral information than a one-band SSS backscatter dataset.…”
Section: Discussioncontrasting
confidence: 52%
“…The quantitative analysis of agreement with the baseline map showed that both methods, despite being very different in terms of input data and methodology, gave comparable results regarding map agreement and error. The map agreement of 67% (OBIA) and 69% (BTM) is acceptable, although lower than what has been reported in some recent studies that mapped reef [28][29][30]. These differences might be related to various factors, e.g., shallow warm-water coral reefs can be mapped with satellite or drone-based optical sensors, which give more spectral information than a one-band SSS backscatter dataset.…”
Section: Discussioncontrasting
confidence: 52%
“…Recent advances in spaceborne and airborne imageries have been successful for improving the habitat discrimination within the complex reefscape [7,8]. The increase in the spatial and spectral resolutions provided by the satellite WorldView-3 has augmented the classification of 10 coral reef classes at 0.3 m spatial resolution based on the 16-band superspectral dataset [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, only five visible spectral bands were appropriate to provide benthic information given the strong light absorption by water from infrared [10]. The green wavelength of the airborne bathymetric Light Detection And Ranging (LiDAR) helped separate the five reef states at 0.5 m point spacing, only based on LiDAR surface and intensity predictors, trained by red-green-blue (RGB) imagery that was acquired from an unmanned aerial vehicle (UAV), called a drone [7]. The emission of electromagnetic radiation (i.e., active remote sensing) in the form of a laser is necessary to penetrate seawater in order been efficient to help create RGB orthomosaics of honeycomb worm reefs [12] and even digital surface models (DSMs) of underwater reef colonies, using a photogrammetric approach [13].…”
Section: Introductionmentioning
confidence: 99%
“…Various mapping technologies have been employed for mapping both shallow and deep areas of the ocean. Passive optical and active blue-green light detection and ranging (LiDAR) remote-sensing systems are used to map shallow benthic habitats [5,6]. Acoustic mapping systems, such as multibeam echo sounding (MBES) instruments, acquire both bathymetry (depth) and backscatter (intensity) data in wide swaths at deeper depths that can be used to map seafloor substrate characteristics [7,8].…”
Section: Introductionmentioning
confidence: 99%